ANALISIS USAHATANI PADI PADA LAHAN CETAK SAWAH DI KABUPATEN TANJUNG JABUNG BARAT - Willya Eka Sari; DMT Napitupulu; Mirawati Yanita (AGRIVET JOURNAL, 2020)
The purpose of this research was to analyze the cost and income  as well as the efficiency of farming on new wetland  field in District Tanjung Jabung Barat. Data was collected by using questionnaire in survey method. The sample size was 66 respondents which are selected in simple random sampling. Data was analysed in cost, revenue and income analysis. Income analysis was followed by efficiency analysis, shows the ratio between revenue and cost (R/C) and the ratio between profit and cost (π/C). Research showed that total cost per hectare of farming on wetland rice field in District Tanjung Jabung Barat was Rp.8.151.822 consisted of real cash Rp.6.504.554 and implicit cost Rp.1.647.268. Incomes and profits earn were Rp.8.618.692 per hectare and Rp.6.971.425 per hectare. R/C ratio on wetland rice field was 2,59 and π/C Ratio was  0,94 show that H0 is rejected and H1 is accepted,  means that the farming on wetland rice field in District Tanjung Jabung Barat is profitable and reasonable to implemented.